2022
DOI: 10.3389/fimmu.2022.918550
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Natural Killer Cells: A Rising Star in Human Pregnancy Regulation

Abstract: Uterine natural killer (uNK) cells are an immune subset located in the uterus. uNK cells have distinct tissue-specific characteristics compared to their counterparts in peripheral blood and lymphoid organs. Based on their location and the pregnancy status of the host, uNK cells are classified as endometrial NK (eNK) cells or decidua NK (dNK) cells. uNK cells are important in protecting the host from pathogen invasion and contribute to a series of physiological processes that affect successful pregnancy, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 184 publications
0
24
0
Order By: Relevance
“…uNK cells have a different phenotype from peripheral pNK cells and have a strong secretory capacity. uNK cells are currently thought to have several possible sources and can differentiate into dNK cells by interacting with the metaphase microenvironment ( 47 ). dNK cells are the most important lymphocytes in the metaphase of early and mid pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…uNK cells have a different phenotype from peripheral pNK cells and have a strong secretory capacity. uNK cells are currently thought to have several possible sources and can differentiate into dNK cells by interacting with the metaphase microenvironment ( 47 ). dNK cells are the most important lymphocytes in the metaphase of early and mid pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that dNK cells play an important role in uterine spiral artery remodeling, placental development, and resistance to microbial infections. In normal pregnancy, the maternal-fetal interface is immune tolerant and activated dNK cells play an important role in defending against infection and preventing intra-placental transmission in the presence of pathogenic microorganisms ( 47 ). dNK cells are recruited in large numbers near the uterine spiral arteries and interact with ligands on the surface of trophoblast cells to activate dNK cells to secrete cytokines and angiogenic factors, induce de-differentiation of spiral arterial vascular smooth muscle cells ( 49 ), as well as promote the recruitment and invasive capacity of EVT cells ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent EPL is a major concern in human reproduction and the focus of much research due to its complex etiology, poor prognosis, and adverse effects on the physical and mental health of pregnant women [ 3 ]. Immune abnormalities, mainly T cell subsets and related miRNA abnormalities, are known to play a vital role in the occurrence of EPL [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Published by Francis Academic Press, UK -9-dNK cells can not only play an immunomodulatory role in the maternal fetal interface [3] , but also play a key role in the regulation of trophoblast invasion and vascular remodeling [4,5] .…”
Section: Introductionmentioning
confidence: 99%